Crescentic flap for the reconstruction of the nose after skin cancer resection. Issue 6 (June 2016) - Arginelli, Federica; Salgarelli, Attilio Carlo; Ferrari, Barbara; Losi, Amanda; Bellini, Pierantonio; Magnoni, Cristina
Abstract: Purpose: Non-melanoma skin cancers are the most frequent skin tumours; in 25.5% of cases, they are reported to affect the nasal area. For an excellent surgical outcome, first of all the radical excision of the lesion is important, with appropriate margins of healthy skin in order to avoid recurrences. Moreover is important to achieve a good aesthetical result, avoiding distortion of the aesthetic units and preserving their functions. Material and methods: We have applied the modified crescentic flap, described by Smadja in 2007, to 24 nasal skin defects left by oncologic surgery. It consists of the crescent-shaped resection of Burow's triangle all around the alar groove that allows the advancement of the flap to the tip of the nose, hiding the scar in the alar groove. Results: The outcome and the long-term follow-up were completely satisfactory both for patients and for surgeons. Conclusion: For skin defects localized in the midline or paramedian line of the dorsum of the nose, the crescentic flap seems to be a good solution to obtain the better aesthetic result with respect to both anatomy and function of the nasal area, sparing the patient a second intervention or an overly invasive procedure.